The role of janus kinases in the treatment of autoimmune skin diseases - Arnold Kukowka; Maria Salmanowicz; Magda Mądra; Bolesław Banach (Polish Pharmaceutical Society, 2021)
The JAK / STAT signaling pathway is a pleiotropic signal transduction pathway for many biochemical substances that are ligands, for example cytokines, growth factor, leptin, erythropoietin or interferons. Numerous skin diseases have autoimmunological origin and are characterized by significant local and systemic inflammation. Janus kinase (JAK) has been observed to play an important role in this process - it processes the signal and activates transcription (STAT). The basic process involved in the development of autoimmune diseases is the differentiation of individual lymphocytes, especially the formation of naive T lymphocytes (Th2, Th1, Th17). Lymphocyte differentiation is mediated by the JAK / STAT signaling pathway. Lymphocytes use cytokines to induce pathological inflammation, and signaling also runs through the JAK / STAT pathway. In diseases that are characterized in our article the most notable cytokines were interferon gamma, tumor necrosis factor-ALPHA and interleukin 22. Mentioned above cytokines are using the JAK/STAT pathway to transduce signal from the outside of cell to the cell nucleus. This information prompted researchers to carefully analyze this issue. In this article we focus on the well-known autoimmune disease of the skin such as: vitiligo, psoriasis, alopecia areata (AA) and atopic dermatitis (AD), in each of this condition the JAK/STAT signaling pathway plays crucial role in their pathomechanisms. Thus the inhibition of this pathway presents itself as a promising target for pharmacological treatment of this diseases. Better understanding of the JAK / STAT pathway triggered the development of targeted Janus kinase inhibitors (jakinibs). JAK inhibitors represent a fairly young and new group of medicines and they are effective therapy in the treatment of many hematological and inflammatory diseases. More and more evidence suggests that JAK inhibitors have utility in the treatment of atopic dermatitis, alopecia areata, psoriasis and vitiligo. JAK inhibitors can be administered orally or topically. Especially treatment with use of the newest and still emerging group of the jakinibs - the selective JAK inhibitors is an interesting horizon for the future. In this article, we review the data on the role of the JAK-STAT pathway in inflammatory dermatoses and analyze the therapeutic benefits of this group of drugs.